Ebstein anomaly in a dog - Silva, Luana Celia Stunitz da; Dahm, Vinicius; Araújo, Letícia Coelho; Gianezini, Estela Dall´Agnol; Grapiglia, Anaisa de Lima; Piva, Manoela Marchezan; Jojima, Flavio Shigueru; Viott, Aline de Marco (Brazilian Journal of Veterinary Pathology, 2025)
Ebstein’s anomaly is a rare congenital cardiac abnormality characterized by an abnormal positioning of the cusps of the tricuspid atrioventricular valve. This study aimed to report the clinical and pathological aspects of the condition in an adult medium-sized mixed-breed dog, treated at a veterinary hospital in Brazil, through clinical evaluation, echocardiography, and post-mortem examination. This case highlights the importance of imaging exams for accurate diagnosis and the formulation of therapeutic strategies aimed at patient survival. To our knowledge, this is the first report of this congenital cardiac anomaly in a medium-sized mixed-breed dog.